Some Findings and Opinions on Religious Turkish Music - Demirtaş, Yavuz (My University, 2022)
The first work written about Religious Turkish Music, which was started to be taught as a course in the 1968-69 academic year at Ankara University, Faculty of Theology, under the name “Turkish Religious Music”, it is a work called “Introduction to Religious Turkish Music”, which was prepared as a textbook by İsmail Baha Sürelsan and published in Ankara in 1972 by the TRT Central Music Department. Both in this work and in works copyrighted thereafter information about the concepts and subjects of Religious Turkish Music was given, and some explanations were made on the subjects that needed explanation. However, unfortunately, a complete unity could not be achieved in these explanations, notably the name of this branch of science and art, the concepts of form and genre, the number and classification of species, etc. there are different expressions on some issues. This situation causes resentment and hesitations in the minds, as well as the emergence of different and contradictory expressions in spoken and written language. This negative situation urgently needs to change into a positive direction, and we think that this will only be possible with the binding decisions of a commission composed of experts. This study, in which we express the controversial concepts and issues of Religious Turkish Music, and the thoughts and recommendations regarding them, is a preliminary information and will contribute to the decisions of the aforementioned commission. Some of our findings, thoughts and recommendations regarding Religious Turkish Music are as follows: It would be more correct to describe Turkish Religious Music as \"Religious Turkish Music\"; It would be more correct to use the concept of \"type\" instead of the word \"form\"; Since there is only one example, it would be more appropriate to describe the Mevlid, Mi'râciyye, Reğâibiyye, Muhammediyye and Ferâciyye as \"Religious Turkish Music Works\"; It would be more accurate to describe Temcîd, Mevlid, Mi'râciyye, Reğâibiyye and Ferâciyye as \"religious ceremonies\" since they contain more than one type; It would be more correct not to describe Müezzinlik, Câmi Müezzinliği, Cumhûr Müezzinliği, Hutbe, İmâmet, Terâvîh Tertîbi, Mahfel Sürmesi and Tardiyye, which are the forms of application of the Kur'ân, Ezân and Kâmet as a separate genre.
Keywords: Folklor